Hak Asasi Manusia dalam Perspektif Hadis dan Hukum Islam - M. Rezky Alsyah Ananta; Fatira Wahidah; Widya Ningsih; Ayyub; Samsu (Gunung Djati Conference Series, 2022)
This study aims to discuss human rights cases in the perspective of hadith and Islamic law. This research has a qualitative approach through descriptive-literature method. The formal object of this research is the science of hadith and Islamic law, while the material object is the hadith about human rights in the history of Bukhari no. 2262. The results and discussion of this study indicate that in human rights, there must be freedom in every aspect. This study concludes that every human being should have freedom of expression in every aspect of his life.